Platelet Membrane‐Camouflaged Magnetic Nanoparticles for Ferroptosis‐Enhanced Cancer Immunotherapy. Issue 22 (27th April 2020) - Jiang, Qin; Wang, Kuang; Zhang, Xingyu; Ouyang, Boshu; Liu, Haixia; Pang, Zhiqing; Yang, Wuli
Abstract: Although cancer immunotherapy has emerged as a tremendously promising cancer therapy method, it remains effective only for several cancers. Photoimmunotherapy (e.g., photodynamic/photothermal therapy) could synergistically enhance the immune response of immunotherapy. However, excessively generated immunogenicity will cause serious inflammatory response syndrome. Herein, biomimetic magnetic nanoparticles, Fe3 O4 ‐SAS @ PLT, are reported as a novel approach to sensitize effective ferroptosis and generate mild immunogenicity, enhancing the response rate of non‐inflamed tumors for cancer immunotherapy. Fe3 O4 ‐SAS@PLT are built from sulfasalazine (SAS)‐loaded mesoporous magnetic nanoparticles (Fe3 O4 ) and platelet (PLT) membrane camouflage and triggered a ferroptotic cell death via inhibiting the glutamate‐cystine antiporter system Xc − pathway. Fe3 O4 ‐SAS @ PLT‐mediated ferroptosis significantly improves the efficacy of programmed cell death 1 immune checkpoint blockade therapy and achieves a continuous tumor elimination in a mouse model of 4T1 metastatic tumors. Proteomics studies reveal that Fe3 O4 ‐SAS @ PLT‐mediated ferroptosis could not only induce tumor‐specific immune response but also efficiently repolarize macrophages from immunosuppressive M2 phenotype to antitumor M1 phenotype. Therefore, the concomitant of Fe3 O4 ‐SAS @ PLT‐mediated ferroptosis with immunotherapy are expected to provide great potential in the clinical treatment of tumor metastasis. Abstract : A new strategy for reinforcing systemic antitumor immunity by using a biomimetic magnetic nanoparticle (Fe3 O4 ‐SAS@PLT) to trigger ferroptosis is proposed, for enhancing the therapeutic effect of programmed cell death 1 immune checkpoint blockade therapy. Fe3 O4 ‐SAS@PLT can repolarize tumor‐assoicated macrophages and continuously eliminate metastatic tumors by enhancing tumor‐related immune response, providing a valuable way of clinically applicable synergistic immunotherapy in cancer.